The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1136/archdischild-2017-314718
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen minute consultation: Fever in children being treated for cancer

Abstract: Fever is a common symptom in children receiving treatment for cancer. Clinicians and families are most concerned about febrile neutropenia, though non-neutropenic fever often causes more challenging treatment dilemmas. This article provides a structured approach to the initial assessment, examination, investigation and risk assessment of children with fever during treatment for childhood cancer. Non-neutropenic fever in children with cancer is not well researched. There are no systematic reviews of its managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…A total of 646 titles and abstracts were reviewed, of which 83 full‐text articles were retrieved. From this, 16 relevant articles, describing 15 studies, were identified for inclusion in this review (Figure ) . No dedicated NNF treatment guidelines were identified in this search.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 646 titles and abstracts were reviewed, of which 83 full‐text articles were retrieved. From this, 16 relevant articles, describing 15 studies, were identified for inclusion in this review (Figure ) . No dedicated NNF treatment guidelines were identified in this search.…”
Section: Resultsmentioning
confidence: 99%
“…In this survey of practice, a number of different empiric antibiotic combinations were used and the presence of a CVC, or known source of infection, had variable impact on decision to start antibiotics. An overview of the treatment approach to NNF is available, which emphasizes adherence to local sepsis or possible CVC‐associated blood stream infection protocols, where relevant …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations